1991
DOI: 10.3168/jds.s0022-0302(91)78192-7
|View full text |Cite
|
Sign up to set email alerts
|

Tall Fescue Endophyte: Effect on Congenital Development and Pup Growth in Mice

Abstract: This study was designed to assess effects of a diet containing endophyte (Acremonium coenophialum)-infected tall fescue seed on litter growth and development in mice. Twenty pairs of mature CD-1 mice were allocated to dietary treatments containing 50% (wt/wt) rodent chow plus either 50% endophyte-infected tall fescue seed or seed that was not infected. At parturition, six pups of approximately equal BW and sex ratio were selected from each litter and fostered to each of the dams for suckling, resulting in four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This pathological condition, known as fescue toxicosis, is generally associated with reduced animal health and performance (Oliver, 2005). Fescue toxicosis is reported to occur in a variety of wild and domestic animals, including birds (Conover and Messmer, 1996;Zavos et al, 1993), meadow voles (Conover, 1998), mice (Varney et al, 1991), rats (Spiers et al, 2005a), sheep (Gadberry et al, 2003), horses (Cross et al, 1995), and cattle (Oliver, 1997). The characteristic changes include reductions in feed intake and growth rate.…”
Section: Introductionmentioning
confidence: 98%
“…This pathological condition, known as fescue toxicosis, is generally associated with reduced animal health and performance (Oliver, 2005). Fescue toxicosis is reported to occur in a variety of wild and domestic animals, including birds (Conover and Messmer, 1996;Zavos et al, 1993), meadow voles (Conover, 1998), mice (Varney et al, 1991), rats (Spiers et al, 2005a), sheep (Gadberry et al, 2003), horses (Cross et al, 1995), and cattle (Oliver, 1997). The characteristic changes include reductions in feed intake and growth rate.…”
Section: Introductionmentioning
confidence: 98%
“…7), indicating a significant negative effect of population density on female sexual maturity in infected plots. Varney et al (1991) also found that a diet of endophyte-infected tall fescue seed delayed the onset of puberty in female mice, although Tannenbaum et al (1998) did not find any difference between infected and uninfected tall fescue seed in suppressing white-footed mouse reproduction.…”
Section: Tall Fescue Endophyte Symbiosis and Plant Community Structumentioning
confidence: 97%
“…The negative effect of the endophyte on laboratory rodents has been well‐documented (Zavos et al , ; Varney et al 1991 a , b ; ; Godfrey et al ), although the effect of endophyte consumption on native small mammals is more variable. For instance, Conover () found that meadow voles ( Microtus pennsylvanicus ) preferred non‐infected leaves to infected leaves and it had no effect on reproduction, but when temperature was increased, they exhibited higher mortality.…”
Section: Primary Exotic Grass Speciesmentioning
confidence: 98%